Collaborative Learning and Its Effect on Statistical Literacy at Sekolah Menengah Pengiran Anak Puteri Hajah Masna, Brunei Darussalam. - Ahmad Fauzi Hamid; Nur Aisyah Rahman (Journal of Science and Mathematics Education, 2026)
Statistical literacy has become an essential competence in secondary education due to its critical role in data-driven decision-making. This study aims to examine the effect of collaborative learning on students’ statistical literacy at Sekolah Menengah Pengiran Anak Puteri Hajah Masna, Brunei Darussalam. A quasi-experimental design with pre-test and post-test was employed, involving an experimental group exposed to collaborative learning strategies and a control group taught using conventional methods. The sample comprised 60 upper secondary students selected through purposive sampling. Data were collected using a validated statistical literacy test and analyzed using paired and independent t-tests to assess significant differences between groups. Findings indicate that students participating in collaborative learning demonstrated significantly higher gains in statistical literacy compared to their peers in the control group. Specifically, collaborative learning enhanced students’ ability to understand statistical concepts, analyze data, interpret graphs, and solve statistical problems effectively. These results suggest that collaborative learning provides a conducive environment for fostering analytical thinking and practical application of statistical knowledge. The study recommends the systematic implementation of collaborative learning strategies within the mathematics curriculum to promote statistical literacy at the secondary level. Furthermore, this research highlights the potential for further studies exploring the impact of collaborative approaches on numerical literacy and critical thinking skills in broader educational contexts. Overall, collaborative learning emerges as a viable pedagogical approach for developing competent, data-literate students capable of navigating an increasingly information-driven world.